Self-Organized Fast Routing Protocol for Radial Underwater Networks. - Hyder, Waheeduddin; Poncela-González, Javier; Luque-Nieto, Miguel Ángel; Otero-Roth, Pablo (MDPI, 2018)
An underwater wireless sensor networks (UWSNs) is an emerging technology for environmental monitoring and surveillance. One of the side effects of the low propagation speed of acoustic waves is that routing protocols of terrestrial wireless networks are not applicable. To address this problem, routing strategies focused on different aspects have been proposed: location free, location based, opportunistic, cluster based, energy efficient, etc. These mechanisms usually require measuring additional parameters, such as the angle of arrival of the signal or the depth of the node, which makes them less efficient in terms of energy conservation. In this paper, we propose a cross-layer proactive routing initialization mechanism that does not require additional measurements and, at the same time, is energy efficient. The algorithm is designed to recreate a radial topology with a gateway node, such that packets always use the shortest possible path from source to sink, thus minimizing consumed energy. Collisions are avoided as much as possible during the path initialization. The algorithm is suitable for 2D or 3D areas, and automatically adapts to a varying number of nodes, allowing one to expand or decrease the networked volume easily.
Keywords: Ondas sonoras; Protocolos de comunicaciones; Sistemas de comunicaciones inalámbricos; Ingeniería - Aparatos e instrumentos; UWSN; Underwater; Location free; Routing protocol; Self-organized; Self-configured; Proactive; Wireless networks